Whitening efficacy of whitening mouth rinses used alone or in conjunction with carbamide peroxide home whitening - Oliveira, J. B.S. [UNESP]; Sarlo, R. S. [UNESP]; Bresciani, E. [UNESP]; Caneppele, T. M.F. [UNESP] (Operative Dentistry, 2017)
Objectives: The aim of this study was to compare the effectiveness of whitening mouth rinses on teeth previously whitened or not, exposed to food dyes. Methods and Materials: One hundred twenty enamel-dentin specimens, 3 mm in diameter, were obtained from bovine incisors. The specimens were stained for 14 days in staining broth. After staining, the initial color reading was performed via a spectrophotometer CM-2600d (Konica Minolta). Half of specimens were submitted to whitening (10% carbamide peroxide [CP]) for 14 days. They were then divided into three groups and were submitted to cycles of staining (five minutes) and mouth rinses (two minutes) for 12 weeks, with the following: CPLI, Listerine Whitening; CP-PL, Plax Whitening; CP-BP, bromelain + papain; CP-DW, deionized water. LI, PL, BP, and DW groups were submitted to the same cited cycles but with no prior bleaching. The color measurements were performed after four, eight, and 12 weeks of treatment with mouth rinses. Data were submitted to repeated measures analysis of variance (ANOVA) and Tukey's test for multiple comparisons, with significance level at 5%. Results: The results showed that the CP-LI, CPPL, LI, and PL groups had greater color change than did the others. The CP-BP and BP groups were similar to CP-DW and DW. Conclusions: We therefore conclude that Listerine Whitening mouth rinse presented the highest bleaching effect, followed by Plax Whitening mouth rinse. Both maintained CP bleaching effect after 12 weeks of dye-rinse cycles. However, none of these rinses were able to produce whitening similar to CP. Bromelain-and papain-containing mouth rinses did not show bleaching effect, being similar to the control groups.